Aspek Hukum Dari Perbuatan "Spoiler" Film pada Platform Sosial - Pradnyana Putra, Ketut Braditya; Marwanto, Marwanto (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2023)
The purpose of this research is to examine the regulation of copyright for film works in Indonesia and to examine the legal aspects of film spoilers on social platforms based on Law 28/2014 through normative legal research methods. The analysis process on legal issues is carried out with the following approaches: historical, statute and conceptual approach until it is found that the legal arrangements related to the copyright of film works in Indonesia have undergone several changes until the last one was promulgated Law 28/2014 as a legal umbrella which formulates the protection of film copyrights. as part of the protected object of cinematographic creation. Furthermore, the act of spoiling a film uploaded on social media can be interpreted as an act of announcing a creation in accordance with Article 9 paragraph (2) of Law 28/2014 so that if it is carried out for commercial purposes and without the permission of the copyright holder or creator, it can be threatened with in accordance with Article 113 of Law 28/2014. As for the act of film spoilers that are uploaded in full on social media with a profit orientation, it can also be considered as an act of film piracy, then the provisions of Article 113 paragraph (4) of Law 28/2014 apply. Tujuan dari dilakukannya penelitian ini adalah untuk mengkaji pengaturan hak cipta karya film di Indonesia dan menelaah aspek hokum dari perbuatan spoiler film di platform social berdasarkan UU 28/2014 melalui metode penelitian hukum normatif. Adapun proses Analisa atas permasalahan hukum dilakukan dengan pendekatan: historical, statute dan conceptual approach hingga didapati yakni pengaturan hukum terkait hak cipta karya film di Indonesia mengalami beberapa kali perubahan hingga yang terakhir diundangkan UU 28/2014 sebagai payung hukum yang dimana merumuskan perlindungan karya cipta film sebagai bagian dari objek ciptaan karya sinematografi yang dilindungi. Selanjutnya, perbuatan spoiler film yang diunggah pada media sosial dapat ditafsirkan sebagai perbuatan pengumuman ciptaan sesuai Pasal 9 ayat (2) UU 28/2014 sehingga bilamana dilakukan dengan tujuan komersial dan tanpa seizin pemegang hak cipta atau pencipta dapat diancam ketentuan Pasal 113 UU 28/2014. Adapun perbuatan spoiler film yang diunggah secara penuh pada media sosial dengan profit orientation juga dapat termasuk sebagai perbuatan pembajakan film, maka terhadapnya berlaku ketentuan Pasal 113 ayat (4) UU 28/2014